Enabling situation awareness with supply chain event management. (1st March 2018) - Vlahakis, George; Apostolou, Dimitris; Kopanaki, Evi
Highlights: Supply chain event management refers to methods that process supply chain events. We present a graph approach to represent supply chain events and their relations. We describe a framework that implements event correlation and situation detection. Key benefits include capability to adapt to dynamic conditions and scalability. Abstract: Supply chain event management exploits synergies between IT and logistics and refers to the set of methods and technologies used to efficiently integrate events from all actors and processes of the supply chain. In the context of supply chain event management, we examine how events can be used to leverage situation awareness. In our approach, situation awareness is facilitated by providing the capability to detect situations, which are represented as correlations between simple events, complex events and supply chain objects (e.g., suppliers, 3PL companies, retailers and material resources). We introduce a two-phase event correlation method which first correlates simple events into complex events and then events with supply chain objects. We describe how the proposed model has been implemented in a software framework and we conduct evaluation tests to examine its situation detection capabilities.